2021
DOI: 10.1371/journal.pone.0250311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imidacloprid and thiamethoxam on the development and reproduction of the soybean aphid Aphis glycines

Abstract: The soybean aphid Aphis glycines Matsumura (Hemiptera: Aphididae) is a primary pest of soybeans and poses a serious threat to soybean production. Our studies were conducted to understand the effects of different concentrations of insecticides (imidacloprid and thiamethoxam) on A. glycines and provided critical information for its effective management. Here, we found that the mean generation time and adult and total pre-nymphiposition periods of the LC50 imidacloprid- and thiamethoxam-treatment groups were sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Ding et al [13] showed that thiamethoxam had a better control impact on corn thrips Frankliniella williamsi Hood (Thysanoptera: Thripidae) than imidacloprid under the same dosing conditions [12,13]. Our previous study also confirmed that imidacloprid had a stronger impact on the growth and reproduction of the soybean aphid population than thiamethoxam at the same concentration [14]. Although they are both neonicotinoids, their heterocyclic structures might lead them to have different pest control effects [11].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Ding et al [13] showed that thiamethoxam had a better control impact on corn thrips Frankliniella williamsi Hood (Thysanoptera: Thripidae) than imidacloprid under the same dosing conditions [12,13]. Our previous study also confirmed that imidacloprid had a stronger impact on the growth and reproduction of the soybean aphid population than thiamethoxam at the same concentration [14]. Although they are both neonicotinoids, their heterocyclic structures might lead them to have different pest control effects [11].…”
Section: Introductionsupporting
confidence: 65%
“…The body no longer needs to synthesize a large amount of antioxidant enzymes and consume a large amount of energy substances to resist the damage of insecticides. Hence, the enzyme activity gradually decreased generation by generation [14,16,30,31]. Furthermore, we found that changes in peroxidase or pyruvate kinase did not accompany changes in trehalase activity.…”
Section: Discussionmentioning
confidence: 71%
“…Thiamethoxam [(EZ)-3-(2-chloro-1,3-thiazol-5yl-methyl)-5-methyl-1,3,5-oxadiazinan-4-ylidene(nitro)amine] is classified according to the pharmacophore as Nnitroguanidineneonicotinoid (Cui et al, 2018). Thiamethoxam is presently one of the most effective chemicals for the control of sucking pests such as aphids (Zhang et al, 2021), whiteflies (Kumar et al, 2019), thrips, some microlepidoptera, and a number of coleopteran species. The result is in line with the findings of Aston et al (2022) who reported that sublethal concentrations of flonicamid and thiamethoxam increase fecundity and phloem-feeding behavior on Myzus persicae.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, sublethal doses of insecticides can cause reduced reproduction, decreased longevity, delayed development, and compromised locomotion or learning in pest insects, beneficial insects, as well as non-target organisms [ 8 , 9 , 10 ]. For examples, sublethal doses of neonicotinoids cause reduced reproduction, body weight, honeydew excretion, and longevity in aphids [ 11 , 12 ]. In beneficial insects, such as honeybees and bumblebees, defects in foraging [ 13 , 14 ], circadian rhythms and sleep [ 15 , 16 , 17 ], learning and memory [ 18 , 19 ], and abnormal neural development [ 19 ] have been detected.…”
Section: Introductionmentioning
confidence: 99%